Adapting Digital Menu To Improve The Customer Experience At UNIMAS Cafeteria - Nur Anisa, Saipudin (Universiti Malaysia Sarawak (UNIMAS), 2020)
The usage of new media technology is increasing nowadays, especially on displaying the food and beverage menus. Menu is a major marketing and communication tool in the restaurant industry as one of the important elements in the ordering system. Therefore, the effectiveness of the digital menu that can manage the ordering system in a fast-paced to make a better streamlining the entire process through implementation of new media to increase the CX (Customer Experience). The purpose of this research is to enhance the customer experience by adapting the digital menu at UNIMAS cafeteria. The implication of these findings is important in order to identify the effectiveness and systematic of digital menu for saves the time on purchasing food or beverage, give a new customer experience in selfservice purchasing by consumption the digital menu.